2021
DOI: 10.3389/fmicb.2021.702093
|View full text |Cite
|
Sign up to set email alerts
|

Hanseniaspora vineae and the Concept of Friendly Yeasts to Increase Autochthonous Wine Flavor Diversity

Abstract: In this perspective, we will explain the concept of “friendly” yeasts for developing wine starters that do not suppress desirable native microbial flora at the initial steps of fermentation, as what usually happens with Saccharomyces strains. Some non-Saccharomyces strains might allow the development of yeast consortia with the native terroir microflora of grapes and its region. The positive contribution of non-Saccharomyces yeasts was underestimated for decades. Avoiding them as spoilage strains and off-flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Hanseniaspora-initiated fermentations have also been shown to reduce final ethanol levels [13], increase overall glycerol concentration [14], modulate acid composition [15], as well as causing a change in anthocyanin content and therefore the colour of the wine [16,17]. One species in particular, namely H. vineae, has shown repeatedly to provide several oenological benefits, which led to the development of a commercially available starter culture by the name of Fermivin VINEAE supplied by Oenobrands [18].…”
Section: Introductionmentioning
confidence: 99%
“…Hanseniaspora-initiated fermentations have also been shown to reduce final ethanol levels [13], increase overall glycerol concentration [14], modulate acid composition [15], as well as causing a change in anthocyanin content and therefore the colour of the wine [16,17]. One species in particular, namely H. vineae, has shown repeatedly to provide several oenological benefits, which led to the development of a commercially available starter culture by the name of Fermivin VINEAE supplied by Oenobrands [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although it was used in many grape varieties as it can be seen in these works, it was never study and related to protein haze in varieties such as Sauvignon blanc. Further studies with this commercial strain should be done to evaluate this aspect in white haze prevention reducing bentonite treatments by its protease capacity or by other extracellular phenomena such as fast cell lysis or increase polysaccharide or mannoprotein synthesis [28]. Therefore, we can conclude that in addition to the before mentioned characteristics of Hanseniaspora vineae yeasts, this yeast can reduce haze in wines.…”
Section: Heat Stability Test (Hst)mentioning
confidence: 87%
“…In the same study, wild Saccharomyces strains with uncommon traits were found and a similar trend of unique traits among Saccharomyces was found in insects associated with grapes and winemaking (Griggs et al, 2021; Stefanini et al, 2012). Vineyards and viniculture are important because wine fermentation is considered to have started before that of beer or bread production, as it does not require inoculum of yeast (Carrau & Henschke, 2021; Padilla et al, 2016). However, brewing and baking might just be as old since no pure cultures were used, mostly back slopping.…”
Section: Ancient and Modern‐day Industries Potentially Improved By Ye...mentioning
confidence: 99%